New record of Ichneumonidae parasitizing the brood of Trypoxylon nitidum Smith, 1856 (Hymenoptera: Crabronidae) - Campos, Melquisedeque Valente; Muniz, David Barros; Silveira, Orlando Tobias (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
We have recorded, for the first time, the ichneumonid Photocryptus concinnus (Brullé) parasitizing the brood of the solitary wasp Trypoxylon (Trypargilum) nitidum Smith in a reused nest (Aculeata) in the state of Pará, Amazonia, Brazil.